A study of impact breakage of single rock specimen using discrete element method - Oladele, Temitope Philip (Department of Chemical Engineering, 2021)
Comminution is a critical stage of mineral processing which aims to reduce the size of ore particles through breakage, consequently increasing the likelihood of the liberation of valuable minerals. However, comminution is highly energy-intensive and an understanding of the key breakage mechanisms has been identified as an important factor in improving the efficiency of the process. Several factors, such as pre-existing cracks, mineralogical composition, ore shape and size are known to affect ore breakage behaviour during breakage. To investigate breakage mechanisms, it is important to be able to determine how individual factor influences the breakage behaviour of rock specimens. However, isolating and investigating individual factors under experimental conditions is challenging and typically impractical. Numerical techniques such as the Bonded Particle Model-Discrete Element Method (BPMDEM) have been developed as a means of investigating in isolation, the effects of different factors on ore breakage behaviour under closely controlled breakage conditions using synthetic rock specimens. This study investigates how individual factors influence rock specimen breakage using BPM-DEM numerical methods. Numerical simulations were conducted using ESyS-particle 2.3.5, an open-source discrete element method (DEM) software package which uses Python-based libraries to generate geometries and simulations and a C++ engine for mathematical computations. Empirical calibration relationships were developed to relate microstructural model parameters to the macroscopic mechanical properties that are typically obtained from standard geotechnical breakage experiments. The robustness of the model was evaluated by considering the sensitivity of fracture measures to the variation of model resolution, size-dependency and macroscopic mechanical properties (Young's modulus and uniaxial compressive strength) of the numerical specimens. A comparative study of single rock specimen breakage using the current BPM-DEM and laboratory SILC experiments carried out by Barbosa et al. (2019) was conducted. The measured fracture force and fracture patterns at different sizes for both cylindrical and spherical synthetic rock specimens were examined. Furthermore, the model was used to study, in isolation, the influence of pre-existing cracks in rock specimens and differing mineralogical compositions upon measurable breakage properties. Numerical rock specimens with pre-existing cracks were constructed using a microcrack approach, while a unique approach with the insertion of "seed points" was developed and demonstrated to construct numerical rock specimens with varying mineralogical compositions. Results from the numerical simulations showed that a high model resolution with a sufficiently large number of DEM-spheres exhibited results with the least deviation and error with respect to fracture measures, and, was therefore considered numerically stable. The dependency of fracture measurements on specimen size showed an expected increase in the measured fracture force as the specimen size increases. The variation of the macroscopic Young's modulus and uniaxial compressive strength against the fracture measures emphasised that the locus of these mechanical properties against the fracture measure can be used to specify a calibration relationship. Results of the comparative study showed that for both cylindrical and spherical rock specimens, the DEM consistently predicted the fragment patterns as well as the increase in the measured fracture force as the specimen size increased. The investigation on the effect of pre-existing cracks revealed that an increasing number of pre-existing cracks in rock specimens necessitated lower fracture force and consequently produced a low amount of new fracture surface area. For the binary phase mineralogical composition in the study, it was found that the fracture force decreased with an increase in the concentration of the softer component due to the increased percentage of weakness in the specimen. It was concluded that, with an appropriate calibration exercise and a realistic specification of material properties from the evaluation study, the DEM as a tool was sufficient to act as a "virtual laboratory" to isolate and study the individual effects of factors that influence ore breakage. The understanding of these results highlighted two important points. Firstly, this study was able to unravel some of the possible causes of the inefficiency in comminution practices, whereby significant amounts of energy can be expended to achieve minimal gains in respect of enhancing liberation due to pre-weakening and mineralogical composition. Secondly, it emphasised some of the causes of the variation observed during ore characterisation on a laboratory breakage device, attributable to pre-weakening and mineralogical composition.